Automatic monitoring of service reliability for web applications: a simulation‐based approach. (29th July 2020) - Kim, Sundeuk; Suh, Ilhyun; Chung, Yon Dohn
Summary: With the recent development of Internet technologies, various web browser‐based applications and services, such as Google and Facebook, are provided. Although many web applications and services make life more efficient for users, they may become unavailable for various reasons. This can have substantial negative impacts on both users and service providers. 24/7/365 web services are especially critical in enterprise environments for establishing their business continuity. For this reason, real‐time service monitoring is the most vital factor for web application providers. Various methods to monitor web applications reliability have been proposed over the past years. However, existing approaches concentrate more on functional testing rather than considering the users perspective. Also, they cannot monitor web applications that rely on web browser application programming interfaces (APIs) or client programmes. In this paper, we propose a novel approach called SAM, which can pinpoint web application failures, including those that require browser APIs or client programmes. We describe the implementation of the SAM system and present the results of an empirical evaluation of a real‐world web application Abstract : Existing approaches for web reliability concentrate on functional testing rather than testing from the user's perspective. In addition, they cannot support the monitoring of web applications that rely on web browser application programming interfaces (APIs) or client programs. We propose methods for monitoring web applications, even requiring additional APIs or programs, based on simulation of users' actions and illustrates the implementation of a system based on the proposed methods.